The Effect of Product Quality and Halal Label Perceptions on Wardah Consumer Preferences: Empirical Study from Nirwana Cosmetics in Mamuju District, Indonesia - Sinar, S.; Fajariani , Nur; Asia, Nur (Golden Ratio of Marketing and Applied Psychology of Business, 2024)
This study aims to determine the effect of product quality variables and perceptions of halal labels on Wardah consumer preferences at Nirwana Cosmetics, Mamuju Regency. The method used in this study is quantitative, with primary data obtained through questionnaires. Respondents in this study were all customers who made purchases at Nirwana Cosmetics, Mamuju Regency. The sample was taken using the accidental sampling technique, with a sample size of 30 respondents. Data analysis in this study used multiple linear regression, validity test, reliability test, t-test, and F-test. The results showed that product quality and perceptions of halal labels had a positive and significant partial effect on Wardah consumer preferences at Nirwana Cosmetics, Mamuju Regency. In addition, product quality and perceptions of halal labels also had a significant simultaneous effect on Wardah consumer preferences at Nirwana Cosmetics, Mamuju Regency.